2012
DOI: 10.1094/pdis-08-11-0664
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Zucchini yellow mosaic virus in Watermelon in Serbia

Abstract: During a survey of cucurbit viruses in the Gornji Tavankut locality (North Backa District), Serbia in June 2011, field-grown (a surface of 1.8 ha) watermelon plants (Citrullus lanatus [Thunb.] Matsum and Nakai) with mild mosaic symptoms were observed. Large numbers of Aphis gossypii were colonizing the crop. A total of 26 samples, six from plants exhibiting mosaic and 20 from asymptomatic plants, were analyzed by double-antibody sandwich-ELISA using polyclonal antisera virus (Bioreba AG, Reinach, Switzerland) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…ZYMV was reported for the first time in 1973 in zucchini plants in Italy, and since then, it has been reported in 18 Mediterranean countries, including France, Israel, Egypt, and Turkey [ 11 , 64 ], as well as in watermelon crops in Serbia, and Bosnia and Herzegovina [ 127 , 128 ]. It has also been reported in other cucurbit species, such as bitter melon in South Korea [ 129 ] and gherkin in India [ 130 ].…”
Section: Geographical Distribution and Occurrence Of Aphid-transmitte...mentioning
confidence: 99%
“…ZYMV was reported for the first time in 1973 in zucchini plants in Italy, and since then, it has been reported in 18 Mediterranean countries, including France, Israel, Egypt, and Turkey [ 11 , 64 ], as well as in watermelon crops in Serbia, and Bosnia and Herzegovina [ 127 , 128 ]. It has also been reported in other cucurbit species, such as bitter melon in South Korea [ 129 ] and gherkin in India [ 130 ].…”
Section: Geographical Distribution and Occurrence Of Aphid-transmitte...mentioning
confidence: 99%
“…Disease symptoms observed this study were consistently similar with those reported in studies in different countries such as Czech Republic (Svoboda andPolák, 2002), Trinidad (Chinnaraja et al, 2016), Sudan (Mohammed et al, 2014), Egypt (Khalifa et al, 2015), Saudi Arabia (Al-Saleh et al, 2014), Japan (Ohtsu et al,. 1985), Malaysia (Fujisawa et al, 1986), Western Australia (Coutts et al, 2011), India (Nagendran et al, 2016), Germany, Serbia, Korea, Australia (Vucˇurovic´ et al, 2012), Illinois (Jossey and Babadoost, 2008), Iran (Hosseini et al, 2007), Poland (Pospieszny et al, 2003) and more. About 10 years after it was first isolated, ZYMV was first recorded by Davis and Yilmaz in 1984 in Turkey and then were reported by various researchers from various geographical locations (Davis and Yılmaz, 1984;Davis, 1986;Yilmaz et al, 1995).…”
Section: B Cmentioning
confidence: 99%
“…Zucchini yellow mosaic virus (ZYMV) is a member of family Potyviridae and is considered the most economically important virus attacking cucurbit plants under ield conditions [1]. The virus was isolated for the irst time in northern Italy [2] and latter from different countries [3][4][5][6][7][8]. In Egypt, ZYMV was isolated from naturally infected squash plants [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Specifi c antiserum was prepared and found to have a titer of 1:409600 as determined by indirect ELISA. [18], Awad, et al [11], Abdel Ghaffar, et al [12], Prieto, et al [19], Younes, [14], Fath-Allah and Ahmed, [15], Usher, et al [20] and Vučurović et al [8] were used as provisional identi ication of the isolated virus.…”
Section: Introductionmentioning
confidence: 99%